Spies in Arabia the Great War and the cultural foundations of Britain's covert empire in the Middle East - Satia, Priya (Oxford University Press, 2008)
At the start of the 20th century, British intelligence agents began to venture in increasing numbers to the Arab lands of the Ottoman Empire, drawn by the twin objectives of securing the route to India and finding adventure and spiritualism in an antique land. 'Spies in Arabia' tracks the dilemma these two different objectives created.